Mennonites and post-colonial African studies
1 online resource (xviii, 298 pages)
Keywords: "This book examines the evolution of post-colonial African Studies through the eyes of Africanists from the Anabaptist (Mennonite and Church of the Brethren) community. The book chronicles the lives of twenty-two academics and practitioners whose work spans from the immediate post-colonial period in the 1960s up to the present day, a period in which decolonization and development has dominated scholarly and practitioner debate. Reflecting the values and perspectives they shared with the Mennonite Central Committee and other church sponsored organizations, the authors consider their own personal journeys and professional careers, the power of the prevailing scholarly paradigms they encountered, and the realities of post-colonial Africa. Coming initially from Anabaptist service programs, the authors ultimately made wider contributions to comparative religion, church leadership, literature, music, political science, history, anthropology, economics and banking, health and healing, public health, extension education, and community development. The personal histories and reflections of the authors provide an important glimpse into the intellectual and cultural perspectives that shaped the work of Africanist scholars and practitioners in the post-colonial period. The book reminds us that the work of every Africanist is shaped by their own life stories"--